Loss of Methyl-CpG–Binding Domain Protein 2 Enhances Endothelial Angiogenesis and Protects Mice Against Hind-Limb Ischemic Injury - Xiaoquan Rao; Jixin Zhong; Shu Zhang; Yushan Zhang; Qilin Yu; Ping Yang; Mong-Heng Wang; David Fulton; Huidong Shi; Zheng Dong; Dao Wen Wang; Cong‐Yi Wang (2011)
Background— Despite intensive investigation, how DNA methylation influences endothelial function remains poorly understood. We used methyl-CpG–binding domain protein 2 (MBD2), an interpreter for DNA methylome–encoded information, to dissect the impact of DNA methylation on endothelial function in both physiological and pathophysiological states. Methods and Results— Human umbilical vein endothelial cells under normal conditions express moderate levels of MBD2, but knockdown of MBD2 by siRNA significantly enhanced angiogenesis and provided protection against H 2 O 2 -induced apoptosis. Remarkably, Mbd2 −/− mice were protected against hind-limb ischemia evidenced by the significant improvement in perfusion recovery, along with increased capillary and arteriole formation. Loss of MBD2 activated endothelial survival and proangiogenic signals downstream of vascular endothelial growth factor signaling characterized by an increase in endothelial nitric oxide synthase (eNOS) and vascular endothelial growth factor receptor 2 expression, along with enhanced extracellular signal-regulated kinase 1/2 activation and BCL-2 expression. Mechanistic studies confirmed the methylation of CpG elements in the eNOS and vascular endothelial growth factor receptor 2 promoter. MBD2 binds to these methylated CpG elements and suppresses eNOS promoter activity. On ischemic insult, key endothelial genes such as eNOS and vascular endothelial growth factor receptor 2 undergo a DNA methylation turnover, and MBD2 interprets the changes of DNA methylation to suppress their expressions. Moreover, MBD2 modulation of eNOS expression is likely confined to endothelial cells because nonendothelial cells such as splenocytes fail to express eNOS after loss of MBD2. Conclusions— We provided direct evidence supporting that DNA methylation regulates endothelial function, which forms the molecular basis for understanding how environmental insults (epigenetic factor) affect the genome to modify disease susceptibility. Because MBD2 itself does not affect the methylation of DNA and is dispensable for normal physiology in mice, it could be a viable epigenetic target for modulating endothelial function in disease states.